(3OhQ GdbfhGJ GdQjGVjI ddCfOjI GdYQHjI h GdCLfHjI ai fTQ GdKbGaI GdQjGVjI h GJLGgGJ GdLeghQ fMhgG (B/ s - (3YdGA CMeO eQJVi YHOGdMejOs; (3ghjOG eUWai (B: s ((3GdbGgQI (B: s (3YdGA CMeO eQJVi YHOGdMejO (B: s, 2021)
(3JSJgOa GdOQGSI GdHMK ai OhQ GdbfhGJ GdJdaRjhfjI ddCfOjI GdQjGVjI GdYQHjI h GdCLfHjI ai fTQ GdKbGaI GdQjGVjI h GdJCKjQ Ydi GdLeghQ(B: (3eY GdHMK ai OhQgG GdGLJeGYi h GdJShjbi GdPi jNOe GfJTGQ GdfGOi h jLPH YOkOG cHjQG ef CaQGO GdLeghQ, h ebGQfI GdbfhGJ GdaVGFjI ddCfOjI GdQjGVjI GdeUQjI HfXjQGJgG GdYGdejI ef CLd JMOjO fbGW GdbhI h GdVYa ajgG h GdGSJaGOI ef GdJLGQH GdYGdejI ai JWhjQgG(B: (3GSJfOJ GdOQGSI Edi fXQjI GdGYJeGO Ydi hSGFd GdEYdGe h fXQjI GdZQS GdKbGai(B. (3h JYO OQGSI hUajI(B: (3GSJNOeJ efgL GdeSM(B: (3ceG GSJNOeJ COGI JMdjd GdeVehf HGdJWHjb Ydi GdHQGeL GdQjGVjI GdoePGYI Ydi bfGJi (B((3GdCgdi h GdReGdc(B): (3h bfGI (B((3djaQHhd(B) (3NdGd GdaJQI ef (B1/8/2020 (3Edi (B1/10/2020: (3Edi LGfH COGI GdGSJHjGf HGdJWHjb Ydi (B602 (3eaQOI ef CaQGO GdLeghQ GdeUQi ef aFI GdTHGH(B. (3JhUdJ GdOQGSI Edi eLehYI ef GdfJGFL, CgegG eG jdj(B: (3Ef fSHI HQGeL bfGI GdCgdi GdJi JgJe HfTQ GdCNHGQ GdQjGVjI GdYQHjI h GdYGdejI JUd Edi (B(55.4%): (3ai Mjf GgJeJ bfGI GdReGdc HfTQ GdCNHGQ GdQjGVjI HfSHI (B(59.3%): (3h GgJeJ bfGI djaQHhd HfTQ CNHGQ GdCMOGK GdQjGVjI h CNHGQ GdeTGgjQ HfSHI (B(45.1%). (3Ef GdbfhGJ GdaVGFjI ddCfOjI GdQjGVjI GdeUQjI JgOa Edi RjGOI fSHI GdeTGgOI h QaY GdCQHGM h GdYed Ydi JMbjb eUGdMgG abW, Ohf GdfXQ ai GdYhGbH GdJi bO JMOK fJjLI deG jJe JbOjeg NdGd gPg GdHQGeL(B. (3Ef eYXe CaQGO GdLeghQ jaVdhf eTGgOI GdbfhGJ GdaVGFjI ddCfOjI GdQjGVjI eY GdCUObGA ai Gdebgi YHQ TGTGJ GdJdaRjhf ai aJQGJ GdeSGA(B: (3dCfg ZGdkHG eG oJYQV GdeHGQjGJ h GdCMOGK GdQjGVjI GdegeI h HQGeL GdJYdjb h GdCSJhOjh GdQjGVi ai GdeSGA(B. (3jQi CaQGO GdYjfI Cf GdbfhGJ GdaVGFjI ddCfOjI GdQjGVjI JJfGhd GdehVhYGJ HTcd SWMi, ceG JgJe HGdLGfH GdEYdGfi h GdJLGQi h dG JgJe HQaY KbGaI GdLeghQ GdQjGVjI, MjK jQi (B(66.2%) (3ef CaQGO GdYjfI Cf GdbfhGJ GdaVGFjI ddCfOjI GdQjGVjI dG JQaY ef KbGaJge GdQjGVjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdEYdGe (B- (3bSe GdEPGYI h GdJdjaRjhfs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GJLGgGJ GdLeghQs; (3GdKbGaI GdQjGVjIs; (3bfhGJ GdCfOjI GdQjGVjIs